Low voltage high performance bulk driven quasi-floating gate based self-biased cascode current mirror. (June 2016) - Raj, Nikhil; Singh, Ashutosh Kumar; Gupta, Anil Kumar
Abstract: A low voltage high performance self-biased cascode current mirror in terms of output resistance and bandwidth is proposed in this paper. The proposed current mirror enhances the output resistance in range of mega ohms and also shows a significant improvement in bandwidth compared to prior arts. The current mirror is designed using bulk-driven technique which helps it to operate at very low supply voltage of ± 0.2 V. To achieve high output resistance, the proposed current mirror uses the super cascode stage at its output. Furthermore, an external capacitor is used which accounts for increasing the bandwidth. Small-signal analysis carried proves the improvement achieved by proposed architecture. The current mirror operates well for wide input current range from 0 to 200  μ A with good linearity and shows the bandwidth of 415 MHz. The observed input and output resistance is 300 Ω and 212 MΩ respectively. Further, the THD and mismatch analysis is carried to prove the robustness of proposed current mirror. The complete analysis of proposed current mirror is shown using HSpice simulations on UMC 0.18 μm technology.